The analysis of public service motivation's influence on job enjoyment and task performance in health workers - Waani, Jane Deasy; Sibarani, Mentiana (Indonesian Journal of Multidisciplinary Science, 2024)
This study is aimed at determining whether there is an influence of public service motivation on the performance of health workers' duties, the influence of work pleasure on the work pleasure of health employees, and the influence on work pleasure through the mediation of work satisfaction. The study is in the form of an observational causative study with a cross sectional design, which aims to determine the influence between variables based on measurement results without intervention. The data were collected through an online questionnaire in April 2024 and analyzed using the PLS-SEM technique to estimate the degree of relationship between variables in the structural model. The results of the analysis of the measurement component (outer model) shows good measurability of all indicators marked by outer loading which is high, as well as the validity of discrimination is quite good. The model has a good degree of accuracy because it is able to account for about two-thirds of all variables. For the management of the hospital, it is recommended to add the criteria of high publicly service motivation as a requirement in employee recruitment. Further research is suggested to complement the model by including factors such as work environment, organizational culture, workload, and superior leadership style as covariates. This could help in identifying unique challenges or opportunities for improving task performance and job satisfaction in different healthcare environments, ultimately leading to more tailored and effective management strategies.